Ideological Struggle in The Principle of Material Legality of the New Indonesian Criminal Code and its Future - Muhammad Azil Maskur; Pujiyono Pujiyono; Irma Cahyaningtyas; Wildan Azkal Fikri; Firsta Rahadatul ‘Aisy (Universitas Negeri Semarang, 2025)
This article emerged from the authors’ hypothesis that the principle of legality in the new Indonesian criminal code is complex to apply due to its reliance on four foundational principles: Pancasila, UUD NRI 45, human rights, and the general principles of law. To prove this hypothesis, the authors use the theory of ideology to analyze the battle of values, ideas, and motives in the four. Based on the authors’ reading, the new Indonesian criminal code has expanded the principle of legality into two, namely, the principle of formal and material legality. In the next instance, the authors identified an ideological struggle in the principle of material legality of the new Indonesian criminal code, which encompasses the clash of personal, political, and legal policy ideologies. Therefore, the principle of material legality is challenging to implement because competing ideologies often counteract one another. Finally, the authors recommend that the principle of legality be enforced by allowing power-sharing in legal jurisdiction between the Indonesian government and Indigenous law people.